A “Prayer Turned Towards the World” or Everyday Mysticism: A Reading of "The Meursault, Investigation" by Kamel Daoud in the Context of Michelde Certeau’s Thought - Thiel-Jańczuk, Katarzyna (2025)
This article analyses the religious issue in Kamel Daoud’s work Meursault, contre-enquęte [The Meursault Investigation]. The starting point of the study is the concept of “reading as poaching” proposed by Michel de Certeau, a French theorist of everyday life. In the first part of the article, we present reading as poaching and view it as a practice derived, among others, from the method of reading employed by Christian mystics. We then relate this concept to Daoud’s understanding of Albert Camus’s L'Étranger [The Stranger] proposed in his book. Reading as poaching involves shifting meaning from one interpretive context to another and is reminiscent of the mystical experience of loss. Therefore, it allows religious experience to be disconnected from a specific religious system (i.e. Islam) and linked to everyday acts of resistance to the absurdity of existence.
Keywords: reading as poaching; everyday life; mysticism